Chemoradiotherapy-related carotid artery inflammation in head and neck cancer patients quantified by [18F]FDG PET/CT. (June 2019) - Chen, Xuguang; Zheng, Yiran; Tatsuoka, Curtis; Muzic, Raymond F.; Okoye, Christian C.; O'Donnell, James K.; Zidar, David; Avril, Norbert; Oliveira, Guilherme H.; Liu, Hongyan; Bucher, Jessica; Machtay, Mitchell; et al.
Highlights: There is a significant increase in carotid artery inflammation due to CRT. CRT-related vascular inflammation was greatest among HPV-positive patients. [ 18 F]FDG uptake may be an early biomarker of CRT-related vascular injury. Abstract: Objectives: Radiotherapy (RT) is associated with an increased risk of cardiovascular disease (CVD), but little is known about the mechanism for vascular injury and methods for early detection. Materials and methods: We conducted a prospective, pilot study of carotid artery inflammation using 18 F-labeled 2-fluoro-2-deoxy-d -glucose ([ 18 F]FDG) PET/CT imaging pre- and 3 months post-RT in head-and-neck cancer (HNC) patients. [ 18 F]FDG uptake by the carotid arteries was measured by the maximum and mean target to background ratio (TBRMAX, TBRMEAN ) and the mean partial volume corrected standardized uptake value (pvcSUVMEAN ). Results: Of the 22 patients who completed both pre and post-RT scans, the majority (82%) had stage III or stage IV disease and received concurrent chemotherapy. TBRMAX, TBRMEAN, and pvcSUVMEAN were all significantly higher 3 months after RT versus before RT with mean difference values (95% CI; p -value) of 0.17 (0.1–0.25; 0.0001), 0.19 (0.12–0.25; 0.0001), and 0.31 g/ml (0.12–0.5; 0.002), respectively. Fifteen patients (68%) had HPV-positive tumors, which were associated with lower pre-RT [ 18 F]FDG signal, but a greater increase in TBRMAX (19% vs 5%), TBRMEAN (21% vs 11%) and pvcSUVMEAN (20% increase vs 3% decrease), compared to HPV negativity. Conclusion: There is a significant increase in carotid artery inflammation in HNC patients due to CRT that amounts to a degree that has previously been associated with higher risk for future CVD events. The subset of patients with HPV-positive tumors experienced the greatest increases in vascular inflammation due to CRT. Carotid [ 18 F]FDG uptake may be an early biomarker of RT-related vascular injury.